2017
DOI: 10.4103/0366-6999.207475
|View full text |Cite
|
Sign up to set email alerts
|

Atopic Dermatitis-like Graft-versus-host Disease and Lichen Planus-like Graft-versus-host Disease

Abstract: Background:Graft-versus-host disease (GVHD) is a common complication of hematopoietic stem cell transplantation. Skin barrier disruption could induce thymic stromal lymphopoietin (TSLP) expression, and the expression of TSLP was increased in lesions of atopic dermatitis (AD)-like GVHD and lichen planus (LP)-like GVHD. This study attempted to investigate the skin barrier function of AD-like GVHD and LP-like GVHD and possible mechanisms.Methods:Eighteen AD-like GVHD patients, 12 LP-like GVHD patients, and 14 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Eriguchi et al (31,32) described that Paneth cells are targeted and markedly reduced during murine GVHD, resulting in decreased α-defensin production. In patients, the expression of defensins during GVHD has been analyzed in only a few studies with limited patient numbers and with controversial results regarding the correlation of defensin expression and GVHD patient outcomes (33)(34)(35). The therapeutic effect of the α-defensin cryptdin-4 (Crp-4) has been investigated in an aGVHD mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…Eriguchi et al (31,32) described that Paneth cells are targeted and markedly reduced during murine GVHD, resulting in decreased α-defensin production. In patients, the expression of defensins during GVHD has been analyzed in only a few studies with limited patient numbers and with controversial results regarding the correlation of defensin expression and GVHD patient outcomes (33)(34)(35). The therapeutic effect of the α-defensin cryptdin-4 (Crp-4) has been investigated in an aGVHD mouse model.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the majority of previously reported cases of eczema‐like GVHD did not have a history of atopy in either recipient or donor 10,11,13 . Of interest, by studying 18 patients with atopic dermatitis‐like GVHD, Li et al demonstrated that similar to patients with spontaneous atopic dermatitis, skin permeability, and antimicrobial barriers are impaired in these patients; however, the mechanism involved is different from that of spontaneous atopic dermatitis 20 . They did not provide a detailed case‐by‐case clinicopathological description of their patients.…”
Section: Discussionmentioning
confidence: 99%
“…In another study of 193 cGVHD patients, pruritus intensity was not associated with cGVHD severity and the presence of pruritus was not associated with survival. 11 In a small observational study from China, Li et al 13 defined the 'pruritus score' as the sum of the VAS (range 0-10) plus a modified duo score (range 0-23) and reported that the mean pruritus score in patients with atopic dermatitis (AD)-like cGVHD (n = 18) was 8.75 higher (11.33 vs. 2.58) than in patients with lichen planus (LP)-like cGVHD (n = 12). However, we did not find any studies that looked in more detail at the average onset of itch or its potential triggers, how patients perceived the quality of itch and how they coped with it.…”
Section: Intensity Predilection Sites and Other Characteristics Of Pr...mentioning
confidence: 99%
“…Of the analysed 13 studies, 9 (69.2%) used binary outcomes ('pruritus' vs. 'no pruritus') to assess pruritus. Only four studies used assessment tools to specify pruritus, including the visual analogue scale (VAS), 13 duo score, 13 numerical ratings scale (NRS) 11,14 and grading scales for pruritus mentioned in the common terminology criteria for adverse events (CTCAE) version 4.0. 15 The VAS and NRS were both scored on a 0-10 scale (0 = no pruritus, 10 = worst pruritus imaginable).…”
Section: Pruritus Assessmentmentioning
confidence: 99%